RAPPROCHEMENT OF LONG-TERM FINANCIAL INTERESTS OF THE SHAREHOLDER AND THE MANAGEMENT OF THE COMPANY - S. I. Lutsenko (Real Economics Publishing House, 2020)
The author considers features of the economic nature of activity of the shareholder in corporate governance and in the control over management. The author offers the standard of the diligent shareholder and the standard of the diligent management as necessary condition for rapprochement of long-term financial interests. Reasonable and diligent realization of the corporate rights, display of interest to company activity will allow the shareholder to receive the information on the concluded transactions. The information on transactions will allow to protect the broken rights in the terms established by the law. The reasonable management within the limits of standard administrative practice should make the maximum efforts for achievement of firm wealth maximization and also consider factors which to a greater or lesser extent influence firm wealth maximization and can be considered as the independent purposes at a certain stage of activity of the company. The company it is necessary to implement the motivation program for rapprochement of long-term financial interests of the shareholder and the management. The motivation program means reception of property benefit from increase in a stock value (share) of the company which possibility of reception is the circumstance stimulating management to act in interests of the company. According to the best practice of corporate governance level of the compensation paid to management, should be sufficient for attraction, motivation and deduction of the persons possessing necessary for company professional skills and qualification, and the compensation system should provide rapprochement of financial interests of directors with long-term financial interests of shareholders. The clause is interdisciplinary, covering elements of corporate governance which are a part of the corporate finance as sciences, and also, the corporate right.